GEOCHEMICAL CHARACTERISTICS OF LATERITE NICKEL DEPOSITS IN BLOCK A PT. KAWEI SEJAHTERA MINING, RAJA AMPAT: KARAKTERISTIK GEOKIMIA ENDAPAN NIKEL LATERIT PADA BLOK A PT. KAWEI SEJAHTERA MINING, RAJA AMPAT - Haluk, Hermina (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
This study was conducted on Kawei Island, Raja Ampat Regency, Southwest Papua Province, focusing on the geochemical characteristics of laterite nickel profiles in the concession area of ​​PT. Kawei Sejahtera Mining (KSM) is a laterite nickel mining company. The study aims to analyze the geochemical characteristics of laterite nickel profiles using field observation methods and X-ray fluorescence (XRF)–based geochemical analysis of 16 laterite zone samples. The results of the analysis show that the laterite nickel deposit profile of Block A consists of overburden, limonite zone, saprolite, and bedrock with varying thicknesses, reaching 16 meters. Geochemical characteristics show an increase in Ni, Fe, Co, MnO, CaO, and Al₂O₃ elements from the bedrock zone to the overburden, while MgO and SiO₂ levels decrease. Nickel levels increase from the overburden to the limonite and saprolite zones but decrease in the bedrock zone.